Pulmonary hypertension and chronic lung disease: where are we headed?. (18th October 2019) - Elia, Davide; Caminati, Antonella; Zompatori, Maurizio; Cassandro, Roberto; Lonati, Chiara; Luisi, Francesca; Pelosi, Giuseppe; Provencher, Steeve; Harari, Sergio
Pulmonary hypertension related to chronic lung disease, mainly represented by COPD and idiopathic pulmonary fibrosis, is associated with a worse outcome when compared with patients only affected by parenchymal lung disease. At present, no therapies are available to reverse or slow down the pathological process of this condition and most of the clinical trials conducted to date have had no clinically significant impact. Nevertheless, the importance of chronic lung diseases is always more widely recognised and, along with its increasing incidence, associated pulmonary hypertension is also expected to be growing in frequency and as a health burden worldwide. Therefore, it is desirable to develop useful and reliable tools to obtain an early diagnosis and to monitor and follow-up this condition, while new insights in the therapeutic approach are explored. New prospective in the management of pulmonary hypertension related to chronic lung diseases http://bit.ly/2lW4CfE